Globalization and its effects on forest diversity: A case study of New Caledonia - Herring, Jamie (University of Ottawa (Canada), 2003)
In the scientific literature pertaining to the world's loss of biodiversity, an extensive amount of research has been undertaken to describe the local biological processes involved in the loss of endangered habitats. However, the social mechanisms that infringe upon these habitats and perpetuate human activities that destroy rare and endangered species has largely been ignored. This thesis is an attempt to discover the social, political and economic causes of habitat loss in the particular case of New Caledonia. Specifically, the extraction of nickel in New Caledonia was examined as a resource that has been central to the island's development history and which has been the cause of the most forest damage. Globalization theory and World-Systems theory have been used in a complementary way to provide a framework for how the integration of New Caledonia into the global economic system over the past 150 years has impacted the island's rare forest systems. Periods of globalization prior to the 1970's were found to have had the most destructive impact on forest habitat than the years following 1975. Greater ecological protections implemented as a result of pressures on France from both global and local environmental groups were found to have increased protection measures for the various forest habitats. However, the destruction of the forests of New Caledonia continues and strong ecological protections that would guarantee the forest's long-term health are still missing.
Keywords: Biology, Ecology.; Sociology, Social Structure and Development.; Environmental Sciences.